Germans in Vojvodina in Times of Establishment of Kingdom of Serbs, Croats, and Slovenes: An Interdisciplinary Approach - Štrangarić, Snežana Z. (Collection of Papers of the Faculty of Philosophy in Priština, 2022)
In this paper, we conducted an interdisciplinary analysis of the process of integration of the German minority in the historical context of the first Yugoslav state, Kingdom of Serbs, Croats, and Slovenes (1918–1929). In 1920, Swabian-German Cultural Association, Kulturbund, was founded as an important factor in preserving the German identity. Even though Kulturbund had interruptions in its activity, in 1924 and 1929, it remained the basic frame for cultural life of the German community during the period between the two wars. Officially, this organization was founded as non-political and loyal to new state, the Kingdom of Serbs, Croats, and Slovenes. The activities of Kulturbund were focused on preservation of German heritage through establishment of cultural institutions such as libraries and bookstores and through organization of cultural events in the area of literature, film, music, and theatre. Kulturbund was most active in Vojvodina. Vojvodina is still a unique model of co-existence of different ethnic groups and cultural patterns, and the German community historically contributed to multiculturalism, multi-confessionalism and multiethnicity of this region. We based our analyses on contributions in the field of sociology on ethnicity, cultural anthropology, and history. Specifically, we found theoretical model of ethnical boundaries, established by Fredrik Barth within the interactional approach to exploring ethnicity, which proved to be useful. Barth’s influential model allowed us to examine the ethnicity from very important aspect—social interaction. In that way, ethnicity is interpreted as a form of social organization of cultural differences. Also, this model implies that ethnical boundaries are flexible, but also resistant, and can be preserved in situations of intensive cultural contacts between different ethnical and cultural groups. According to Barth, the factors with the most influence to the strengthening of ethnical boundaries are social changes on the international level, such as wars.
Keywords: Kulturbund; Germans; identity; ethnic minority; Vojvodina